A Review of Quantitative Characterization of Phase Interface Dynamics and Optimization of Heat Transfer Modeling in Direct Contact Heat Transfer - Mingjian Wang; Jianxin Xu; Shibo Wang; Hua Wang (Energies)
Direct contact heat transfer as an efficient heat recovery method. It is used in the fields of waste heat recovery, nuclear engineering, desalination, and metallurgy. This study examined two key issues of the direct contact heat transfer process: difficulty in accurately characterizing the dynamics of the flow field–phase interface; and difficulty in coupling the complex multiphysics fields involved in direct contact heat transfer. This paper systematically reviews the spatio-temporal evolution characteristics and quantitative characterization methods of bubble dynamics in direct contact heat transfer processes, with an in-depth discussion on theoretical modeling approaches and experimental validation strategies for coupled heat and mass transfer mechanisms within multiphase flow systems. An interesting phenomenon was found in this study. Many scholars have focused their research on optimizing the working conditions and structure of direct contact heat transfer in order to improve heat transfer efficiency. The non-equilibrium phenomenon between the two phases of direct contact heat transfer has not been thoroughly studied. The non-equilibrium phase transition model can deepen the understanding of the microscopic mechanism of interfacial energy exchange and phase transition dynamics in direct contact heat transfer by revealing the transient characteristics and non-equilibrium effects of heat and mass transfer at dynamic interfaces. Based on the findings above, three key directions are proposed to guide future research to inform the exploration of direct contact heat transfer mechanisms in future work: 1 dynamic analysis of multi-scale spatio-temporal coupling mechanisms, 2 accurate quantification of unsteady interfacial heat transfer processes, and 3 synergistic integration of intelligent optimization algorithms with experimental datasets.